Large room-temperature elastocaloric effect in a bulk polycrystalline Ni-Ti-Cu-Co alloy with low isothermal stress hysteresis. (December 2020) - Yang, Zhi; Cong, Daoyong; Yuan, Yuan; Li, Runguang; Zheng, Hongxing; Sun, Xiaoming; Nie, Zhihua; Ren, Yang; Wang, Yandong
Highlights: A new robust elastocaloric material with outstanding properties was developed. This material shows a large room-temperature, low-hysteresis elastocaloric effect. The adiabatic temperature change during unloading is up to −14.4 K. The stress hysteresis of the superelastic stress-strain curve is as low as 60 MPa. A very high coefficient of performance up to 19 is achieved on the material level. Abstract: Development of high-performance advanced elastocaloric materials is essential for the execution of elastocaloric refrigeration that can be an environment-friendly and high-efficiency substitute for the widely used traditional vapor-compression cooling technology. Here we have developed a bulk polycrystalline Ni-Ti-Cu-Co shape memory alloy exhibiting large elastocaloric effect, low stress hysteresis and room-temperature working temperature, all of which are of great importance to and urgently demanded for high-efficiency room-temperature elastocaloric refrigeration. This newly developed (Ni42.5 Ti50 Cu7.5 )99 Co1 alloy shows a large room-temperature elastocaloric effect with directly measured adiabatic temperature change up to −14.4 K during unloading. The stress hysteresis of the isothermal superelastic stress-strain curve is as low as 60 MPa when the maximum tensile strain is 2.7%. Owing to the large elastocaloric effect and low stress hysteresis, a very high coefficient of performance up to 19 is achieved on the material level. This newly developed (Ni42.5 Ti50 Cu7.5 )99 Co1 alloy is a robust candidate for efficient elastocaloric refrigeration. Advanced in-situ synchrotron high-energy X-ray diffraction technique was employed to reveal the phase transformation sequence and to accurately determine the crystal structure of different phases, based on which the lattice compatibility between the transforming phases was evaluated and the phase transformation strain was predicted, providing in-depth fundamental understanding of the martensitic transformation in this newly developed alloy. This work could be useful for designing high-performance elastocaloric materials for solid-state cooling applications. Graphical abstract: Image, graphical abstract